Global Research Landscape linking Oral and Ocular Health: A Bibliometric Analysis (2000-2025) (Bangladesh Journal of Medical Science, 2026)
This study examined how research connecting oral and ocular health has developed over the past two decades. Interest in this topic has grown because certain dental procedures, immunerelated disorders, and severe drug reactions can affect both the mouth and the eyes. To understand how the field has evolved, a search was carried out in the Dimensions database for studies published between 2000 and 2025. After applying the inclusion criteria, 351 articles were analyzed using bibliometric tools to explore publication trends, citation patterns, country contributions, and connections between studies. The results show a steady publication growth peaking in 2024, though with limited citation impact. Oral Surgery, Oral Medicine, Oral Pathology, and Oral Radiology, and BMC Oral Health are identified as the most productive journals. The United States and India are the most productive countries. Highly cited works focus on ocular complications from dental local anesthesia, occupational risks, autoimmune mucosal diseases, and severe drug reactions. Research trends indicate an evolution from procedural complications to systemic and immune-mediated disorders, and, more recently, to infectious and vascular conditions. The most studied health conditions with both oral and ocular manifestations include Sturge–Weber syndrome, diabetes, Sjögren’s syndrome, Behçet’s disease, mucous membrane pemphigoid, orbital apex syndrome, and cavernous sinus thrombosis. Bibliographic coupling identifies case reports related to ocular complications of dental anesthesia, including vision loss, diplopia, ophthalmoplegia, ptosis, Horner’s syndrome, and Harlequin syndrome. Limited overlap between citation-coupled and highly cited studies suggests contemporary research diverges from earlier foundational work. These findings indicate that oral–ocular health connections constitute a growing yet fragmented research domain that requires greater interdisciplinary collaboration to advance clinical and translational applications.Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 718-731